1997
DOI: 10.2307/3579539
|View full text |Cite
|
Sign up to set email alerts
|

Issues in the Comparison of Risk Estimates for the Population in the Techa River Region and Atomic Bomb Survivors

Abstract: Plutonium production in the former Soviet Union began in 1949 at the Mayak Production Association located between the cities of Chelyabinsk and Ekaterinbourg in the southern Ural mountains about 1200 km east to Moscow. During the first few years of Mayak's operation, almost 30,000 people living on the banks of the Techa River received significant internal and external exposures as a consequence of the release of large quantities of radioactive materials from Mayak. Studies of levels of radioactive contaminatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 7 publications
0
25
0
Order By: Relevance
“…Radiation-induced leukemia in humans was first reported early in the 20th century (1)(2)(3)(4). Since then, numerous studies of atomic bomb survivors, people working or living near nuclear power plants, radiologists, and radiotherapy patients have shown that certain doses of both acute and fractionated radiation exposure result in a high risk of leukemia and lymphoma (1)(2)(3)(4)(5)(6)(7). Furthermore, the risk of secondary radiation treatment-related lymphoma and leukemia is a clinical problem (6).…”
Section: Introductionmentioning
confidence: 99%
“…Radiation-induced leukemia in humans was first reported early in the 20th century (1)(2)(3)(4). Since then, numerous studies of atomic bomb survivors, people working or living near nuclear power plants, radiologists, and radiotherapy patients have shown that certain doses of both acute and fractionated radiation exposure result in a high risk of leukemia and lymphoma (1)(2)(3)(4)(5)(6)(7). Furthermore, the risk of secondary radiation treatment-related lymphoma and leukemia is a clinical problem (6).…”
Section: Introductionmentioning
confidence: 99%
“…The combined exposure studies are not suitable for the derivation of MRLs. An increase in the incidence of leukemia was reported for Techa River individuals receiving estimated bone marrow doses, attributed to radioactive strontium, in excess of 10 rem (0.1 Sv) (Kossenko 1996;Kossenko et al 1997Kossenko et al , 2000Kossenko et al , 2002. Dystrophic lesions of the skeleton were observed in individuals with mean radiation doses to the surface of bone in excess of 200 rem (2 Sv) (Akleyev et al 1995).…”
Section: Oral Mrlsmentioning
confidence: 99%
“…In contrast, the Techa River population that was exposed to contaminated water and food as a result of releases from a nuclear weapons facility exhibited a significant increase in the incidence of leukemia (Kossenko 1996;Kossenko et al 1997Kossenko et al , 2000Kossenko et al , 2002. An excess of leukemia cases (0.85 excess cases per 10,000 person-year Gy (95% CI: 0.2; 1.5) was observed in groups of individuals with estimated bone marrow doses in excess of 10 rem (0.1 Sv), and the risk of mortality from leukemia increased with increasing dose (Kossenko, 1997(Kossenko, , 2002.…”
Section: Cancermentioning
confidence: 99%
See 2 more Smart Citations